ACUTE ISCHEMIC STROKE: ENDOVASCULAR REPERFUSION AND EARLY REHABILITATION - A PERSONALIZED IMAGING-GUIDED APPROACH - Ahmadovich, Kilichev Farruh; Anvarovna, Yarmuhamedova Nargiza; Mansur, Aliyev (Research Focus International Scientific Journal, 2026)
Acute ischemic stroke remains one of the leading causes of mortality and long- term disability worldwide. While intravenous thrombolysis with tissue plasminogen activator has significantly improved early stroke management, its effectiveness is limited by a narrow therapeutic window and incomplete recanalization in large vessel occlusions. Recent advances in endovascular reperfusion techniques have transformed the treatment landscape, offering higher rates of successful vessel recanalization and improved clinical outcomes. Modern approaches including mechanical thrombectomy, aspiration thrombectomy, and intra-arterial thrombolysis have demonstrated superior efficacy, particularly when combined with intravenous thrombolytic therapy. In addition, the development of novel fibrinolytic agents and adjunctive methods such as ultrasound-enhanced thrombolysis has further expanded therapeutic possibilities. Alongside reperfusion strategies, early initiation of rehabilitation plays a critical role in enhancing neurological recovery, promoting neuroplasticity, and reducing long-term disability. The integration of advanced endovascular interventions with early rehabilitation represents a comprehensive and patient-centered approach to the management of acute ischemic stroke. Future perspectives emphasize individualized, imaging-guided treatment strategies and multidisciplinary care to optimize functional outcomes and extend therapeutic time windows.